Higher contact tackles from upright tacklers increases the risk of head Injury removals in elite women`s rugby union: a case-control study - Tucker, R.; Smith, A.; Hester, B.; Falvey, E. (Journal of Science and Medicine in Sport, 2025)
Objectives To describe tackle characteristics associated with increased risk of Head Injury Assessment (HIA) removals in elite women`s Rugby Union.